Moral encounters in tourism: the role of regret - Jiang, Fenfen (2025)
This thesis examines the role of regret in moral tourism encounters. Regret is a highly valued emotion due to its psychological benefits, involving the facilitation of behavioural change and insights into the self (Saffrey et al., 2008). This points to the potential of regret in promoting moral practices and moral self-development. However, little has been discussed regarding the moral significance of regret. In this regard, tourism provides a suitable research context. Tourism is a moral field of experience through encounters with different cultures and people (MacCannell, 2011). Thus, this study focuses on tourists’ regret experience involved in moral issues or dilemmas to explore how tourists engage their sense of morality in tourism encounters, including the emotional construction of regret experience and its subjective meanings.